Chemical immune conization of precancerous cervical lesions awakens immune cells and restores normal HPV negative and abnormal proliferation - Liu, Xueping; Yu, Baofa; Gao, Feng; Jing, Peng; Zhang, Peicheng; Zheng, Guoqin; Zhang, Xiaomin (Frontiers in Immunology, 2024)
Background: Cervical cancer is one of the most common and deadly cancers in women, for who with persistent infection of high-risk human papillomavirus (HPV). Current treatment of cervical cancer involves radical hysterectomy, radiotherapy and chemotherapy or a combination. Objective: We investigated if hapten enhanced intratumoral chemotherapy (HEIC) was effective in boosting immunity for effective treatment of precancerous cervical lesions and HPV infection Study Design: We used single-cell RNA sequencing (scRNA-Seq) to obtain transcriptome profiles of 40239 cells from biopsy of precancerous cervical lesions at the cervix directly from one patient before the start of HEIC and about 1 week after HEIC. The blood samples were taken at same time as biopsies. We compared the expression characteristics of malignant epithelial cells and immune cells, including Epithelial Cells, Ecs, Fibroblasts, Mural Cells, Tcells, Bcells, TandNK Neutrophils, Mast Cells, MPs, and Platelets, as well as the dynamic changes in cell percentage and cell subtype heterogeneity. Results: Intratumoral injection of chemotherapy drug plus hapten induces acute immune response in precancerous cervical lesions with HPV, and further awakens immune cells to prevent abnormal proliferation of the precancerous cells. Conclusion: HEIC provides a potential treatment method for cervical cancer and HPV infection tailored to each patient's condition.